First Year Winner: The Mobilization of Moral Regulation: The LGBT Purge and Homophobia as a National Security Practice: HIST 1086, Vice and Bad Behaviours in North America. Course Director: Marcel Martel - Ruivo, Adriana-Isabel (Noteworthy: The LA&PS Writing Prizes, 2025)
How we recognize and commemorate history can be as important as the historical moments themselves. “The Mobilization of Moral Regulation: The LGBT Purge and Homophobia as a National Security Practice” is the result of a first-year History assignment that asks students to produce the text for what would be an Ontario Heritage Trust historical plaque observing a worthy moment in Canadian history. Acknowledging Canadian Prime Minister Justin Trudeau’s 2017 formal apology to the LGBTQ2+ community as a catalyst for healing and reconciliation between its members and the greater population, this assignment is more than just a 100-word plaque. Adriana Isabel-Ruivo conducts incisive research on the state repression Canada enacted upon such communities during the 1950s and 1960s, laying bare sociological factors at work as profound as the Cold War and its overlaying politico-economic ideologies. Leveraging victim testimony and an appraisal of the limits of forgiveness in terms of actual reparations and historical recognition, this analysis doesn’t just provide a poignant draft for a plaque that would memorialize an important historical time; it tells a story of open-ended resistance and survival that calls for further action.